2016
DOI: 10.1177/0960327116660751
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effects of anti-tuberculosis drugs on HepG2 cell bioenergetics

Abstract: Tuberculosis (TB) is an intractable chronic infection. Disease treatment with anti-TB drugs remains challenging due to drug-induced hepatotoxicity. The toxicity of the anti-TB drugs rifampicin (RIF), isoniazid (INH) and pyrazinamide (PZA) either alone or in combination was investigated in HepG2 cells. Assays of intracellular adenosine triphosphate (ATP) levels at 4-, 24- and 48-h post-exposure to gradient concentrations of RIF, INH and PZA were conducted. Drug-induced effects on mitochondrial membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Anti-tuberculosis drugs (e.g. rifampicin, isoniazid) induce mitophagy in HepG2 cells [57], and clinical concentrations of efavirenz promote mitophagy [58]. In contrast, perfluorooctane sulfonate impaired mitophagy in HepG2 cells [59], and amitriptyline impaired mitophagy in human hepatocytes [60].…”
Section: Discussionmentioning
confidence: 99%
“…Anti-tuberculosis drugs (e.g. rifampicin, isoniazid) induce mitophagy in HepG2 cells [57], and clinical concentrations of efavirenz promote mitophagy [58]. In contrast, perfluorooctane sulfonate impaired mitophagy in HepG2 cells [59], and amitriptyline impaired mitophagy in human hepatocytes [60].…”
Section: Discussionmentioning
confidence: 99%
“…These previous studies have established the relation between the [2Fe-2S]-containing FECH and iron levels in murine erythroleukemia cells, macrophage cell line RAW 264.7, and K562 cells and have shown that FECH is downregulated in ironlimiting conditions and upregulated in iron-replete conditions. However, there have been reports of the relation between FECH and iron levels in the liver hepatoma cell line HepG2/C3A, which is commonly used to study hepatotoxicity in vitro and has been used to demonstrate the toxicity of rifampicin and isoniazid at millimolar concentrations (Elmorsy et al, 2017;Shih et al, 2013;Singh et al, 2011;Tostmann et al, 2008). Additionally, because the FBS added to cell culture medium contained iron at a concentration of 26 mM, the cell culture medium conditions required for iron-mediated rescue by exogenous iron administration had Figure 2.…”
Section: Iron Levels Modulate Human Fech Protein Levelsmentioning
confidence: 99%
“…Rifampicin is a known inducer of many metabolizing enzymes; some metabolites produce through these reactions are toxic and their accumulation would result in the induction of liver injury or immune responses [31]. Rifampicin could also cause the accumulation of reactive oxygen species (ROS) as a result of mitochondrial toxicity [32]. The liver injury caused by chemicals or infectious agents if not treated may progress to liver fibrosis, cirrhosis and liver failure [7].…”
Section: Discussionmentioning
confidence: 99%